PENINGKATAN KAPASITAS INOVASI MODEL BISNIS MOBILE MARKET FORKOM UMKM KAPANEWON NGEMPLAK KABUPATEN SLEMAN - Indah Widowati; Wulandari Dwi Etika Rini; Heni Handri Utami; Karyono; Anang Susanto; Avinda Sofitaria; Aninda Sekar Zahra; Aqmarina Laili Asyrafi; Gerardus Hanandika Dishatama (Universitas Merdeka Madiun, 2025)
Internal community service (PbM-U) through the “Mobile Market Business Model Innovation Program of the Ngemplak Sub-district MSME Forum in Sleman Regency”. The objectives of this program are (1) Increasing the independence of MSMEs through the development of creative, innovative and local resource-based MSME products, (2) Optimizing the capabilities of MSMEs in the use of digital technology. This program is conducted through mentoring, training, and hands-on practice. Each activity prioritizes Focus Group Discussions (FGDs) with active participant involvement. At the end of the program, an evaluation will be conducted and the concept of sustainable service will be realized through delegation and mentoring of young people in partner areas to become pioneers for other MSMEs.